From Teaching Collection to Experimental Learning Space: Education on a Higher Level at the Universalmuseum Joanneum - Holzer-Kernbichler, Monika (Tudásmenedzsment, 2026)
This paper examines the Universalmuseum Joanneum in Graz as an educational institution from its foundation in 1811 to the present, focusing on the continuity and transformation of its relationship with universities and its role in art education. Founded by Archduke Johann as a “national educational institution” accessible to all social classes, the museum emerged from Enlightenment ideals that sought to connect theory and practice, research and teaching, and collections with public education. In its early decades, the Joanneum functioned primarily as a teaching and research institution closely linked to emerging scientific disciplines and higher education in Graz. The article traces how this educational mission shifted over time through the expansion of art collections, the professionalization of art history, and the establishment of specialized exhibition spaces such as the Neue Galerie. Particular attention is given to the development of art education and mediation practices since the opening of the Kunsthaus Graz in 2003. Selected case studies demonstrate contemporary forms of collaboration with universities that integrate artistic, curatorial, performative and inclusive approaches. Methodologically, the study follows a qualitative and interpretative framework, combining historical analysis with case studies and institutional reflection. The analysis highlights the persistence of the Joanneum’s educational mandate and positions the museum today as a participatory, research-based space of shared knowledge production at the intersection of museum, university and society.